High-temperature-resistant geotextile and preparation method thereof
By using phenylenediamine amide polyether ether ketone and maleic anhydride grafting reaction in geotextiles, combining carboxyl groups and epoxy groups to modify polyether sulfone, and using phosphate ester and ionic liquid to modify aluminum nitride, as well as silane groups and dopamine to modify silicon carbide, a multi-layer interface structure is formed, which solves the problem of degradation in performance of traditional geotextiles in high temperature environments and achieves higher thermal stability and mechanical properties.
Patent Information
- Application Number
- CN202510036254.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-09
AI Technical Summary
Traditional geotextiles exhibit thermal deformation, melting or reduced strength in high temperature environments, resulting in a decrease in their effectiveness in soil enhancement and soil and water conservation, and their application in high temperature or high heat environments is not sufficient to meet engineering design requirements.
Polyether ether ketone is amended by phenylenediamine and maleic anhydride is grafted to form a gradient polar group distribution, improving interface binding strength and compatibility; at the same time, the carboxyl group and epoxy group modified polyether sulfone is introduced to form a complementary network, enhancing the toughness and interface binding ability of the matrix. Phosphate is used to provide polar binding sites on the surface of aluminum nitride, and ionic liquid forms a thermal conductivity network to improve thermal conductivity; silane groups provide chemical bonding sites on the surface of silicon carbide, and dopamine forms a secondary structure, enhancing interface binding capabilities.
It improves the thermal stability and mechanical properties of geotextiles in high temperature environments, enhances its binding force with the soil, and ensures the quality and safety of engineering applications under high temperature conditions.
Smart Images

Figure CN119640501A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials and relates to a high temperature resistant geotextile and a preparation method thereof. Background Art
[0002] Geotextile is a functional material widely used in civil engineering, environmental protection and construction. It is mainly used to enhance soil stability, control soil erosion, and provide filtration and drainage functions. The design goal of these materials is to improve the performance of the soil by providing a physical barrier, thereby improving the durability and safety of the project. The main materials of geotextiles are usually polymers, such as polypropylene, polyester, etc. These materials are widely used due to their excellent mechanical properties, corrosion resistance and economy.
[0003] Polypropylene and polyester are the most commonly used materials for geotextiles. Polypropylene is widely used in various civil engineering projects because of its light weight, high strength and good chemical resistance. Polyester is favored for its excellent tensile strength and heat resistance, especially for applications that need to withstand large loads. However, traditional geotextiles perform well in conventional civil engineering applications, but have obvious shortcomings in applications under high temperature environments.
[0004] Many geotextiles have relatively poor performance under high temperature conditions. Common materials such as polypropylene and polyester are prone to thermal deformation, melting or strength loss in high temperature environments. This thermal deformation not only causes dimensional instability of the geotextile, but may also affect its bonding with the soil, thereby reducing its effectiveness in soil reinforcement and soil and water conservation. In certain specific application scenarios, such as road construction and tunnel engineering, geotextiles are often required to work for a long time in high temperature or high heat environments. Under these conditions, traditional geotextiles may not meet the design requirements, resulting in a decline in project quality and an increase in safety hazards. For example, if the geotextile melts or deforms, it may cause soil loss and structural collapse, which directly affects the safety and service life of the project; in addition, for example, in landfill operations under high temperature environments, geotextiles need to withstand high temperatures and pressures from the fill. If the strength of the geotextile is insufficient, it may cause its function to fail, which in turn causes a series of engineering problems. Therefore, the fragility of traditional materials under high temperature conditions limits their potential for application in some key projects, especially in those fields with high temperature and pressure requirements, such as the construction of waste landfills and soil stabilization in thermal power plants. Summary of the invention
[0005] In view of the above problems, the object of the present invention is to provide a high temperature resistant geotextile and a preparation method thereof. First, polyetheretherketone is aminated by phenylenediamine and grafted with maleic anhydride to form a gradient polar group distribution, thereby improving the interface bonding strength and compatibility; at the same time, carboxyl and epoxy groups are introduced to modify polyethersulfone to form a complementary network, thereby enhancing the toughness and interface bonding ability of the matrix. Secondly, phosphate provides polar binding sites on the surface of aluminum nitride, and ionic liquid forms a thermal conductive network thereon, thereby improving the thermal conduction efficiency; silane groups provide chemical bonding sites on the surface of silicon carbide, and dopamine forms a secondary structure thereon, thereby enhancing the interface bonding ability. Finally, the amino-maleic anhydride structure of aminopolyetheretherketone and the carboxyl-epoxy structure of polyethersulfone are interspersed with each other to form an interpenetrating network structure, thereby improving the toughness and thermal stability of the matrix, while the multi-level interface structure of aluminum nitride and silicon carbide helps to uniformly transfer stress and improve interface firmness.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a high temperature resistant geotextile, the method for preparing the high temperature resistant geotextile comprising:
[0008] S1: dispersing polyetheretherketone in concentrated sulfuric acid to obtain a polyetheretherketone dispersion, adding p-phenylenediamine after stirring to obtain a pre-reaction liquid, reacting at a constant temperature to obtain a reaction liquid A, pouring the reaction liquid A into deionized water and stirring to obtain a pre-treated precipitate, filtering, washing, and vacuum drying to obtain an amino polyetheretherketone intermediate; mixing the amino polyetheretherketone intermediate with maleic anhydride and dibenzoyl peroxide initiator to obtain a reaction liquid B, melting and reacting under nitrogen protection, cooling and granulating to obtain a modified polyetheretherketone;
[0009] S2: Mixing polyethersulfone and N-methylpyrrolidone, adding 4-aminobenzoic acid to obtain reaction solution C, stirring the mixture to react, pouring the mixture into deionized water, filtering to obtain pretreated polyethersulfone, washing the mixture, and vacuum drying to obtain a carboxylated polyethersulfone intermediate; melt-mixing the carboxylated polyethersulfone intermediate with glycidyl methacrylate under a nitrogen atmosphere, cooling and granulating the mixture to obtain a modified polyethersulfone;
[0010] S3: mixing aluminum nitride with tetrahydrofuran, adding dodecyl phosphate and triethylamine to obtain a reaction solution D, stirring the reaction, centrifuging to obtain a first modified aluminum nitride, dispersing the first modified aluminum nitride in an acetonitrile solution of [BMIM]PF6 to obtain a reaction solution E, ultrasonically treating the first modified aluminum nitride, and vacuum drying the first modified aluminum nitride.
[0011] S4: mixing silicon carbide powder with an ethanol / water mixed solution, adding polyvinyl pyrrolidone to obtain a mixed solution, adding a mixed coupling agent after ultrasonic dispersion to obtain a reaction solution F, refluxing and centrifuging to obtain a first treated silicon carbide, dispersing it in a Tris buffer, adding dopamine hydrochloride, stirring at room temperature, filtering, washing, and vacuum drying to obtain a modified silicon carbide;
[0012] S5: Add modified polyetheretherketone, modified polyethersulfone and antioxidant into a high-speed stirrer for mixing, add modified silicon carbide and modified aluminum nitride to mix to obtain a mixture, add the mixture into a twin-screw extruder for extrusion, collect the extrudate for melt spinning, lay the obtained spun yarn on the mesh curtain of a web forming machine, consolidate it through a needle punching machine to obtain a rough geotextile, adjust the tension through a tension frame, and enter a roll-forming machine for edge trimming and roll-forming to obtain a high temperature resistant geotextile.
[0013] As a preferred technical solution of the present invention, in step S1, the mass ratio of the polyetheretherketone to concentrated sulfuric acid is 1:15-20, for example, it can be 1:15, 1:15.5, 1:16, 1:16.5, 1:17, 1:17.5, 1:18, 1:18.5, 1:19, 1:19.5 or 1:20, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] In some optional embodiments, the mass ratio of p-phenylenediamine to polyetheretherketone is 3-4:100, for example, it can be 3:100, 3.1:100, 3.2:100, 3.3:100, 3.4:100, 3.5:100, 3.6:100, 3.7:100, 3.8:100, 3.9:100 or 4:100, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] In some optional embodiments, the temperature of the isothermal reaction of the pre-reaction liquid is 75-85°C, for example, it can be 75.0°C, 76.0°C, 77.0°C, 78.0°C, 79.0°C, 80.0°C, 81.0°C, 82.0°C, 83.0°C, 84.0°C or 85.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] In some optional embodiments, the isothermal reaction time of the pre-reaction liquid is 4-6 hours, for example, it can be 4.0 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours, 5.0 hours, 5.2 hours, 5.4 hours, 5.6 hours or 6.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] In some optional embodiments, the volume ratio of the reaction liquid A to deionized water is 1:4-5, for example, it can be 1:4, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9 or 1:5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In some optional embodiments, the pretreated precipitate is washed until the supernatant pH is 6.5-7.5, for example, it can be 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4 or 7.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] In some optional embodiments, the vacuum drying temperature is 70-80°C, for example, it can be 70.0°C, 71.0°C, 72.0°C, 73.0°C, 74.0°C, 75.0°C, 76.0°C, 77.0°C, 78.0°C, 79.0°C or 80.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] In some optional embodiments, the vacuum drying time is 10-12h, for example, it can be 10.0h, 10.2h, 10.4h, 10.6h, 10.8h, 11.0h, 11.2h, 11.4h, 11.6h, 11.8h or 12.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] In some optional embodiments, the mass ratio of the amino polyetheretherketone intermediate to maleic anhydride is 100:2.5-3.5, for example, it can be 100:2.5, 100:2.6, 100:2.7, 100:2.8, 100:2.9, 100:3.0, 100:3.1, 100:3.2, 100:3.3, 100:3.4 or 100:3.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] In some optional embodiments, the mass ratio of the amino polyetheretherketone intermediate to the dibenzoyl peroxide initiator is 100:0.3-0.7, for example, it can be 100:0.3, 100:0.35, 100:0.4, 100:0.45, 100:0.5, 100:0.55, 100:0.6, 100:0.65 or 100:0.7, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] In some optional embodiments, the temperature of the melting reaction of the reaction liquid B is 275-285°C, for example, it can be 275.0°C, 276.0°C, 277.0°C, 278.0°C, 279.0°C, 280.0°C, 281.0°C, 282.0°C, 283.0°C, 284.0°C or 285.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] In some optional embodiments, the melting reaction time of the reaction liquid B is 20-30 min, for example, it can be 20.0 min, 21.0 min, 22.0 min, 23.0 min, 24.0 min, 25.0 min, 26.0 min, 27.0 min, 28.0 min, 29.0 min or 30.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] In some optional embodiments, the nitrogen flow rate is 100-150 mL / min, for example, it can be 100.0 mL / min, 105.0 mL / min, 110.0 mL / min, 115.0 mL / min, 120.0 mL / min, 125.0 mL / min, 130.0 mL / min, 135.0 mL / min, 140.0 mL / min, 145.0 mL / min or 150.0 mL / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] As a preferred technical solution of the present invention, in step S2, the mass ratio of the polyethersulfone to N-methylpyrrolidone is 1:10-15, for example, it can be 1:10, 1:10.5, 1:11, 1:11.5, 1:12, 1:12.5, 1:13, 1:13.5, 1:14, 1:14.5 or 1:15, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In some optional embodiments, the mass ratio of the polyethersulfone to 4-aminobenzoic acid is 100:3.5-4.5, for example, it can be 100:3.5, 100:3.6, 100:3.7, 100:3.8, 100:3.9, 100:4.0, 100:4.1, 100:4.2, 100:4.3, 100:4.4 or 100:4.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In some optional embodiments, the stirring reaction temperature of the reaction liquid C is 130-140°C, for example, it can be 130.0°C, 131.0°C, 132.0°C, 133.0°C, 134.0°C, 135.0°C, 136.0°C, 137.0°C, 138.0°C, 139.0°C or 140.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In some optional embodiments, the stirring reaction time of the reaction liquid C is 4-6h, for example, it can be 4.0h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.2h, 5.4h, 5.6h or 6.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In some optional embodiments, the temperature of vacuum drying after washing the pretreated polyethersulfone is 60-70°C, for example, it can be 60.0°C, 61.0°C, 62.0°C, 63.0°C, 64.0°C, 65.0°C, 66.0°C, 67.0°C, 68.0°C, 69.0°C or 70.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In some optional embodiments, the vacuum drying time after washing the pretreated polyethersulfone is 12-14 hours, for example, it can be 12.0 hours, 12.2 hours, 12.4 hours, 12.6 hours, 12.8 hours, 13.0 hours, 13.2 hours, 13.4 hours, 13.6 hours, 13.8 hours or 14.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In some optional embodiments, the mass ratio of the carboxylated polyethersulfone intermediate to glycidyl methacrylate is 100:3-4, for example, it can be 100:3.0, 100:3.1, 100:3.2, 100:3.6, 100:3.4, 100:3.5, 100:3.6, 100:3.7, 100:3.8, 100:3.9 or 100:4.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In some optional embodiments, the temperature for melt mixing of the carboxylated polyethersulfone intermediate and glycidyl methacrylate is 235-245°C, for example, 235.0°C, 236.0°C, 237.0°C, 238.0°C, 239.0°C, 240.0°C, 241.0°C, 242.0°C, 243.0°C, 244.0°C or 245.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In some optional embodiments, the time for melt mixing of the carboxylated polyethersulfone intermediate and glycidyl methacrylate is 15-20 min, for example, 15.0 min, 15.5 min, 16.0 min, 16.5 min, 17.0 min, 17.5 min, 18.0 min, 18.5 min, 19.0 min, 19.5 min or 20.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] As a preferred technical solution of the present invention, in step S3, the mass ratio of aluminum nitride to tetrahydrofuran is 1:10-15, for example, it can be 1:10, 1:10.5, 1:11, 1:11.5, 1:12, 1:12.5, 1:13, 1:13.5, 1:14, 1:14.5 or 1:15, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional embodiments, the mass ratio of aluminum nitride to dodecyl phosphate is 100:3-4, for example, it can be 100:3.0, 100:3.1, 100:3.2, 100:3.3, 100:3.4, 100:3.5, 100:3.6, 100:3.7, 100:3.8, 100:3.9 or 100:4.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional embodiments, the mass ratio of aluminum nitride to triethylamine is 100:0.5-1.5, for example, it can be 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1.0, 100:1.1, 100:1.2, 100:1.3, 100:1.4 or 100:1.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In some optional embodiments, the stirring reaction temperature of the reaction liquid D is 60-70°C, for example, it can be 60.0°C, 61.0°C, 62.0°C, 63.0°C, 64.0°C, 65.0°C, 66.0°C, 67.0°C, 68.0°C, 69.0°C or 70.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In some optional embodiments, the stirring reaction time of the reaction liquid D is 5-7h, for example, it can be 5.0h, 5.2h, 5.4h, 5.6h, 5.8h, 6.0h, 6.2h, 6.4h, 6.6h, 6.8h or 7.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] In some optional embodiments, the mass ratio of the first modified aluminum nitride to [BMIM]PF6 is 100:2-3, for example, it can be 100:2.0, 100:2.1, 100:2.2, 100:2.3, 100:2.4, 100:2.5, 100:2.6, 100:2.7, 100:2.8, 100:2.9 or 100:3.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In some optional embodiments, the concentration of the [BMIM]PF6 acetonitrile solution is 1-2%, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] In some optional embodiments, the power of the ultrasonic treatment of the reaction solution E is 200-300 W, for example, it can be 200 W, 210 W, 220 W, 230 W, 240 W, 250 W, 260 W, 270 W, 280 W, 290 W or 300 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In some optional embodiments, the ultrasonic treatment time of the reaction solution E is 1-2h, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] In some optional embodiments, the vacuum drying temperature is 55-65°C, for example, it can be 55.0°C, 56.0°C, 57.0°C, 58.0°C, 59.0°C, 60.0°C, 61.0°C, 62.0°C, 63.0°C, 64.0°C or 65.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In some optional embodiments, the vacuum drying time is 8-10 h, for example, it can be 8.0 h, 8.2 h, 8.4 h, 8.6 h, 8.8 h, 9.0 h, 9.2 h, 9.4 h, 9.6 h, 9.8 h or 10.0 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] As a preferred technical solution of the present invention, in step S4, the volume ratio of ethanol to water in the ethanol / water mixed solution is 9:1-7:3, for example, it can be 9:1, 8:2, 7:3, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional embodiments, the mass ratio of silicon carbide to ethanol / water mixed solution is 1:10-15, for example, it can be 1:10.0, 1:10.5, 1:11.0, 1:11.5, 1:12.0, 1:12.5, 1:13.0, 1:13.5, 1:14.0, 1:14.5 or 1:15.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In some optional embodiments, the mass ratio of polyvinyl pyrrolidine to silicon carbide is 1-2:100, for example, it can be 1:100, 1.1:100, 1.2:100, 1.3:100, 1.4:100, 1.5:100, 1.6:100, 1.7:100, 1.8:100, 1.9:100, 2:100, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] In some optional embodiments, the ultrasonic power of the mixed solution is 300-400 W, for example, it can be 300 W, 310 W, 320 W, 330 W, 340 W, 350 W, 360 W, 370 W, 380 W, 390 W or 400 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In some optional embodiments, the ultrasonic time of the mixed solution is 30-40 min, for example, it can be 30.0 min, 31.0 min, 32.0 min, 33.0 min, 34.0 min, 35.0 min, 36.0 min, 37.0 min, 38.0 min, 39.0 min or 40.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In some optional embodiments, the mass ratio of KH550 to KH570 in the mixed coupling agent is 1-2:1, for example, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] In some optional embodiments, the mass ratio of silicon carbide to the mixed coupling agent is 100:2-3, for example, it can be 100:2.0, 100:2.1, 100:2.2, 100:2.3, 100:2.4, 100:2.5, 100:2.6, 100:2.7, 100:2.8, 100:2.9 or 100:3.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In some optional embodiments, the reflux temperature of the reaction liquid F is 65-75°C, for example, it can be 65.0°C, 66.0°C, 67.0°C, 68.0°C, 69.0°C, 70.0°C, 71.0°C, 72.0°C, 73.0°C, 74.0°C or 75.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In some optional embodiments, the reflux time of the reaction liquid F is 5-7h, for example, it can be 5.0h, 5.2h, 5.4h, 5.6h, 5.8h, 6.0h, 6.2h, 6.4h, 6.6h, 6.8h or 7.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In some optional embodiments, the concentration of the Tris buffer is 0.05-0.1M, for example, it can be 0.05M, 0.055M, 0.06M, 0.065M, 0.07M, 0.075M, 0.08M, 0.085M, 0.09M, 0.095M or 0.1M, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In some optional embodiments, the solid-liquid mass ratio of the first treated silicon carbide to Tris buffer is 1:8-10, for example, it can be 1:8.0, 1:8.2, 1:8.4, 1:8.6, 1:8.8, 1:9.0, 1:9.2, 1:9.4, 1:9.6, 1:9.8 or 1:10.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some optional embodiments, the mass ratio of the first treated silicon carbide to dopamine hydrochloride is 100:1.5-2.5, for example, it can be 100:1.5, 100:1.6, 100:1.7, 100:1.8, 100:1.9, 100:2.0, 100:2.1, 100:2.2, 100:2.3, 100:2.4 or 100:2.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In some optional embodiments, the stirring time at room temperature is 8-10 h, for example, it can be 8.0 h, 8.2 h, 8.4 h, 8.6 h, 8.8 h, 9.0 h, 9.2 h, 9.4 h, 9.6 h, 9.8 h or 10.0 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In some optional embodiments, the vacuum drying temperature is 45-55°C, for example, it can be 45.0°C, 46.0°C, 47.0°C, 48.0°C, 49.0°C, 50.0°C, 51.0°C, 52.0°C, 53.0°C, 54.0°C or 55.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In some optional embodiments, the vacuum drying time is 10-12h, for example, it can be 10.0h, 10.2h, 10.4h, 10.6h, 10.8h, 11.0h, 11.2h, 11.4h, 11.6h, 11.8h or 12.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] As a preferred technical solution of the present invention, in step S5, the screw extrusion speed is 150-200rpm, for example, it can be 150rpm, 155rpm, 160rpm, 165rpm, 170rpm, 175rpm, 180rpm, 185rpm, 190rpm, 195rpm or 200rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In a second aspect, the present invention provides a high temperature resistant geotextile, wherein the high temperature resistant geotextile comprises the following components in parts by weight:
[0063]
[0064] In some optional embodiments, the amount of the modified polyetheretherketone is 65-70 parts, for example, it can be 65 parts, 65.5 parts, 66 parts, 66.5 parts, 67 parts, 67.5 parts, 68 parts, 68.5 parts, 69 parts, 69.5 parts or 70 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] In some optional embodiments, the amount of the modified polyethersulfone is 25-30 parts, for example, it can be 25 parts, 25.5 parts, 26 parts, 26.5 parts, 27 parts, 27.5 parts, 28 parts, 28.5 parts, 29 parts, 29.5 parts or 30 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In some optional embodiments, the amount of modified aluminum nitride is 2-3 parts, for example, it can be 2 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts or 3 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] In some optional embodiments, the amount of modified silicon carbide is 3-4 parts, for example, it can be 3 parts, 3.1 parts, 3.2 parts, 3.3 parts, 3.4 parts, 3.5 parts, 3.6 parts, 3.7 parts, 3.8 parts, 3.9 parts or 4 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] In some optional embodiments, the amount of the antioxidant is 0.5-0.8 parts, for example, it can be 0.5 parts, 0.55 parts, 0.6 parts, 0.65 parts, 0.7 parts, 0.75 parts or 0.8 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] The present invention selects polyetheretherketone as the main material. Polyetheretherketone is a semi-crystalline polymer with a high glass transition temperature and melting point. Its good thermal stability enables it to maintain its mechanical properties unchanged in a high temperature environment, ensuring that the geotextile is not prone to aging or failure in extreme environments; secondly, polyetheretherketone has extremely strong resistance to chemical corrosion and can withstand the erosion of strong acids, strong alkalis and organic solvents, which is very critical for the long-term use of geotextiles in harsh environments; in addition, it has a high modulus and excellent tensile strength while maintaining a certain toughness. This characteristic makes it suitable as a base material for geotextiles, providing reliable mechanical properties for the final product.
[0070] Polyetheretherketone is dispersed in concentrated sulfuric acid, and the strong oxidizing and swelling effects of sulfuric acid are used to chemically pretreat polyetheretherketone. Under the action of concentrated sulfuric acid, the benzene ring structure of polyetheretherketone is activated, and the benzene ring is more likely to react with p-phenylenediamine. The introduction of amino groups can significantly improve the chemical reactivity of polyetheretherketone, providing active sites for subsequent reactions with maleic anhydride.
[0071] The amino polyetheretherketone reacts with maleic anhydride, and more polar groups can be introduced through the acylation of maleic anhydride: under the action of dibenzoyl peroxide initiator, the amino polyetheretherketone and maleic anhydride undergo grafting reaction to form modified polymer chains, which not only improves the heat resistance and antioxidant properties of polyetheretherketone, but the silver soil with the same polar group also enhances the surface energy of the modified polyetheretherketone, thereby facilitating the interfacial bonding with inorganic fillers or other polymers.
[0072] There is a synergistic effect between the two modification methods of polyetheretherketone: the amino group provides reactive sites, and maleic anhydride preferentially undergoes grafting reaction at the amino site, thereby forming a gradient distribution of polar groups and improving the interface bonding strength and compatibility.
[0073] Polyethersulfone is used as another matrix material in the present invention. Polyethersulfone is an amorphous polymer material with a high glass transition temperature and can maintain excellent dimensional stability at high temperatures. Compared with polyetheretherketone, polyethersulfone has better flexibility, which can provide certain plasticity and fracture resistance for geotextiles. At the same time, its flexibility makes the modified composite material more suitable for the melt spinning process, and the fibers are not easy to break during the molding and needle punching consolidation process; in addition, polyethersulfone has excellent antioxidant properties. When exposed to an oxidizing atmosphere or ultraviolet rays, its molecular chain structure is very stable and has good weather resistance, which can increase the service life of the geotextile outdoors.
[0074] In the present invention, polyethersulfone is modified: by introducing 4-aminobenzoic acid, polyethersulfone is modified into a carboxylated polyethersulfone intermediate, and its reactivity and polarity are enhanced: the amino group in 4-aminobenzoic acid reacts with polyethersulfone to form an amide structure, and the carboxyl group enhances the polarity and interfacial compatibility of polyethersulfone through hydrogen bonds or ionic bonds. Carboxylation enhances the hydrophilicity of polyethersulfone and its interfacial bonding ability with inorganic fillers.
[0075] Secondly, the carboxylated polyethersulfone is reacted with glycidyl methacrylate to introduce ether bonds or hydroxyl groups through the ring-opening reaction of the epoxy group, thereby further improving the cross-linking density and functionalization degree of the polyethersulfone: under molten conditions, the carboxylated polyethersulfone and glycidyl methacrylate undergo a ring-opening esterification reaction to generate a cross-linking structure, which increases the intermolecular bonding force, further improves the heat resistance of the modified polyethersulfone, and also enhances the flexibility of the polyethersulfone.
[0076] The carboxyl and epoxy groups introduced by the two modification methods of polyethersulfone form a complementary network, providing a multi-level cross-linking structure and effectively enhancing the toughness and interface bonding ability of the matrix.
[0077] There is a synergistic enhancement effect between polyetheretherketone and polyethersulfone: polyetheretherketone has higher heat resistance, while polyethersulfone provides certain flexibility and low processing temperature. The combination of the two can improve the processing performance and flexibility of the material while ensuring high temperature resistance; polyetheretherketone provides higher modulus and strength, while polyethersulfone can increase the toughness and fracture resistance of the composite material, so that the final geotextile has both high strength and is not easy to break in practical applications; at the same time, after modification, both polyetheretherketone and polyethersulfone can introduce polar groups to form a good interface with functional fillers, effectively improving the thermal conductivity and strength of the composite material, and the amino-maleic anhydride structure of polyetheretherketone and the carboxyl-epoxy network of polyetherketone interpenetrate to form an interpenetrating network structure, improving the toughness and thermal stability of the matrix; polyetheretherketone has stronger chemical stability, while polyethersulfone supplements its flexibility and antioxidant capacity, so that the final composite material shows higher durability in a variety of chemical environments.
[0078] The present invention selects aluminum nitride as one of the fillers. Aluminum nitride has a high thermal conductivity coefficient and is one of the best thermal conductivity among common fillers. It can effectively transfer and dissipate heat, which makes it very suitable for use in composite materials that require high thermal conductivity. Geotextiles may need to quickly remove heat in high-temperature industrial environments to avoid performance degradation caused by local overheating. The high thermal conductivity of aluminum nitride can significantly improve the thermal management performance of composite materials.
[0079] Although aluminum nitride has high thermal conductivity, its resistivity is extremely high, making it an excellent thermal conductor and electrical insulator. At the same time, aluminum nitride has a high decomposition temperature and good thermal and chemical stability at high temperatures, so it is suitable for geotextiles in high temperature environments. At the same time, aluminum nitride is non-toxic and pollution-free, and is environmentally friendly in processing and actual use.
[0080] The use of dodecyl phosphate can transform the surface of aluminum nitride from hydrophilic to hydrophobic through surface modification. The dodecyl phosphate molecules chemically adsorb to the surface of aluminum nitride through the phosphate group to form a covalent bond or an ionic bond, while the long-chain alkyl part provides hydrophobicity, thereby improving its dispersibility with the polymer matrix; [BMIM]PF6 is used to further modify the surface of aluminum nitride to provide a stable interface effect. The ionic liquid uniformly covers the surface of aluminum nitride through physical adsorption or chemical bonding, reducing the agglomeration phenomenon between particles and providing a certain lubrication effect. This improves the dispersion stability of aluminum nitride and enables the thermal conductivity of the modified aluminum nitride in the matrix to be fully utilized. Phosphate provides a strong polar binding site, and the ionic liquid forms a thermal conductive network on the phosphate layer, thereby forming an ordered interface layer and improving the thermal conduction efficiency.
[0081] Silicon carbide is selected as another filler in the present invention. Silicon carbide is an ultra-high temperature ceramic material that can maintain structural stability and provide strength in extremely high temperature environments; secondly, silicon carbide has extremely high hardness and high strength and high modulus properties, which makes it an ideal reinforcing filler; silicon carbide exhibits extremely strong chemical stability in most acidic, alkaline and oxidizing environments, especially under high temperature or extreme chemical conditions, which can extend the service life of composite materials; in addition, silicon carbide has a high thermal conductivity that can improve the thermal conductivity of composite materials, but its thermal expansion coefficient is very low, which matches polyetheretherketone and polyethersulfone, and can effectively reduce the thermal stress of composite materials in high temperature environments; and silicon carbide can form a dense protective film in a zinc oxide environment, thereby improving its antioxidant ability.
[0082] The surface of silicon carbide is treated with a silane coupling agent. The silane group in the coupling agent reacts with the hydroxyl group on the surface of silicon carbide to generate Si-O-Si bonds. The organic end of the coupling agent forms an interface with the matrix, thereby improving the interface bonding between silicon carbide and the organic matrix material. The dispersibility of silicon carbide particles and the interface bonding force with the matrix are enhanced. The modified silicon carbide can more effectively improve the strength and heat resistance of the composite material.
[0083] At the same time, dopamine is used to modify the surface-modified silicon carbide: dopamine undergoes self-polymerization reaction under alkaline conditions, and its catechol and amine groups form hydrogen bonds or covalent bonds with the surface of silicon carbide to generate a stable coating. By utilizing the polymerization ability of dopamine, a layer of polydopamine coating is formed on the surface of the surface-modified silicon carbide, thereby enhancing the functionalization of silicon carbide. The silane group provides a chemical bonding site, and polydopamine forms a secondary structure on the silane layer on this basis, thereby constructing a multi-level interface structure and enhancing its interface bonding ability.
[0084] There is also a synergistic enhancement effect between aluminum nitride and silicon carbide: the high thermal conductivity of aluminum nitride and silicon carbide significantly improves the overall thermal conductivity of the composite material, and the dopamine layer of modified silicon carbide and the ionic liquid layer of aluminum nitride can form a heat conduction channel, further improving its thermal conductivity efficiency. Aluminum nitride provides a higher heat dissipation capacity, and silicon carbide supplements thermal conductivity and provides thermal expansion matching; in terms of mechanical properties, aluminum nitride enhances the rigidity and dimensional stability of the composite material, while silicon carbide improves wear resistance and impact resistance, and the two together improve the comprehensive mechanical properties of the composite material; at the same time, aluminum nitride and silicon carbide both have extremely high heat resistance and can work together in high temperature environments to avoid failure of the composite material due to thermal degradation or thermal expansion; surface-modified aluminum nitride and silicon carbide can form a strong interface bond with the matrix to ensure uniform distribution of fillers and avoid agglomeration, thereby improving the processing performance and final performance of the composite material.
[0085] The modified polymer and the functional filler are uniformly mixed and a composite material is formed by extrusion and spinning. During the extrusion process, the polar groups of the modified polymer and the surface groups of the inorganic filler are combined through hydrogen bonds or chemical bonds to form a uniform composite structure, which provides a good mixing effect and ensures the dispersion of the filler in the matrix.
[0086] Through the melt spinning method, the modified polymer is stretched into fibers at high temperature, providing excellent mechanical properties and high temperature resistance; needle punching consolidation enhances the mechanical bonding between fibers, improves the tensile strength and dimensional stability of the geotextile; the melt spinning and needle punching consolidation processes form a structurally stable fiber web.
[0087] Compared with the prior art, the present invention has the following beneficial effects:
[0088] (1) Polyetheretherketone is aminated with p-phenylenediamine to provide active sites for subsequent reactions, and maleic anhydride is grafted on the amino sites to form a gradient polar group distribution, thereby improving its interfacial bonding strength and compatibility; at the same time, carboxyl and epoxy groups are introduced to modify polyethersulfone, and the carboxyl and epoxy groups form a complementary network, thereby providing a multi-level cross-linking structure and enhancing the toughness and interfacial bonding ability of the matrix;
[0089] (2) Phosphate provides strong polar binding sites on the aluminum nitride surface, and the ionic liquid forms a heat-conducting network on the phosphate layer, forming an ordered interface layer to improve the heat conduction efficiency; the silane group introduced on the silicon carbide surface provides chemical bonding sites, and dopamine forms a secondary structure on the silane layer. The two construct a multi-level interface structure to enhance its interface bonding ability;
[0090] (3) The amino-maleic anhydride structure of polyetheretherketone and the carboxyl-epoxy structure of polyethersulfone interpenetrate each other to form an interpenetrating network structure, which improves the toughness and thermal stability of the matrix; the ionic liquid layer of aluminum nitride and the dopamine layer of silicon carbide form a heat conduction channel, making the interface structure multi-layered and the stress transfer more uniform; and the polar groups of the matrix form multiple forces with the filler surface, making the interface structure stronger. BRIEF DESCRIPTION OF THE DRAWINGS
[0091] Figure 1 A flow chart of a method for preparing a high temperature resistant geotextile provided in Example 1 of the present invention;
[0092] Figure 2 This is a scanning electron microscope image of the spinning provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0093] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0094] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products.
[0095] Example 1
[0096] like Figure 1 As shown, this embodiment provides a high temperature resistant geotextile and a preparation method thereof, wherein the high temperature resistant geotextile includes the following components in parts by weight:
[0097]
[0098] The preparation method specifically comprises the following steps:
[0099] S1: Disperse polyetheretherketone in concentrated sulfuric acid to obtain a polyetheretherketone dispersion, wherein the mass ratio of polyetheretherketone to concentrated sulfuric acid is 1:17, stir, add p-phenylenediamine in a mass ratio of 3.8:100 to polyetheretherketone to obtain a pre-reaction solution, react at a constant temperature of 80°C for 5 hours to obtain a reaction solution A, pour it into deionized water and stir to obtain a pre-treated precipitate, wherein the volume ratio of reaction solution A to deionized water is 1:4.5, filter and wash until the pH of the supernatant is 7, and vacuum dry at 70°C 12h to obtain an amino polyether ether ketone intermediate; the amino polyether ether ketone intermediate is mixed with maleic anhydride and dibenzoyl peroxide initiator to obtain reaction solution B, wherein the mass ratio of the amino polyether ether ketone intermediate to maleic anhydride is 100:3, and the mass ratio of the amino polyether ether ketone intermediate to dibenzoyl peroxide initiator is 100:0.5, and the reaction is carried out at 280°C for 25min under nitrogen protection at a flow rate of 125mL / min, and the modified polyether ether ketone is obtained by cooling and granulation;
[0100] S2: polyethersulfone and N-methylpyrrolidone are mixed at a mass ratio of 1:10, 4-aminobenzoic acid is added to obtain a reaction solution C, wherein the mass ratio of polyethersulfone to 4-aminobenzoic acid is 100:4, and after stirring for reaction, the mixture is poured into deionized water, wherein the stirring temperature is 138°C and the time is 5 hours, and the pretreated polyethersulfone is obtained by filtration, and after washing, the mixture is vacuum dried at 65°C for 13 hours to obtain a carboxylated polyethersulfone intermediate; the carboxylated polyethersulfone intermediate is melt-mixed with glycidyl methacrylate under a nitrogen atmosphere, wherein the mass ratio of the carboxylated polyethersulfone intermediate to glycidyl methacrylate is 100:3.8, the melt-mixing temperature is 235°C, and the time is 18 minutes, and the modified polyethersulfone is obtained by cooling and granulation;
[0101] S3: Aluminum nitride and tetrahydrofuran are mixed in a mass ratio of 1:12, and dodecyl phosphate and triethylamine are added to obtain a reaction solution D, wherein the mass ratio of aluminum nitride to dodecyl phosphate is 100:3, and the mass ratio of aluminum nitride to triethylamine is 100:1. The mixture is stirred and reacted at 68°C for 6 hours, and a first modified aluminum nitride is obtained after centrifugal separation. The first modified aluminum nitride is dispersed in an acetonitrile solution of [BMIM]PF6 with a concentration of 1.5% to obtain a reaction solution E, wherein the mass ratio of the first modified aluminum nitride to is 100:3, and the mixture is subjected to an ultrasonic treatment at a power of 260 W for 1 hour and then vacuum dried, wherein the vacuum drying temperature is 60°C and the time is 9 hours, to obtain a modified aluminum nitride;
[0102] S4: SiC powder is mixed with an ethanol / water mixed solution with a volume ratio of 7:3, wherein the mass ratio of SiC to the ethanol / water mixed solution is 1:13, polyvinyl pyrrolidone is added in a mass ratio of 1.5:100 to SiC to obtain a mixed solution, and after ultrasonic dispersion at a power of 350 W for 30 min, a mixed coupling agent is added to obtain a reaction solution F, wherein the mass ratio of KH550 to KH570 in the mixed coupling agent is 2:1, and the mass ratio of SiC to the mixed coupling agent is 100:2.5, and the reaction solution F is obtained after refluxing and centrifuging at 70° C. for 6 h, and the first treated SiC is obtained, which is dispersed in a Tris buffer with a concentration of 0.07 M, wherein the solid-liquid mass ratio of the first treated SiC to the Tris buffer is 1:10, and dopamine hydrochloride is added, wherein the mass ratio of the first treated SiC to dopamine hydrochloride is 100:2, and the reaction solution is stirred at room temperature for 9 h, filtered, washed, and vacuum dried at 50° C. for 11 h to obtain modified SiC;
[0103] S5: Add modified polyetheretherketone, modified polyethersulfone and antioxidant 1010 into a high-speed stirrer for mixing, add modified silicon carbide and modified aluminum nitride to mix to obtain a mixture, add the mixture into a twin-screw extruder for extrusion, wherein the screw extrusion speed of the twin-screw extruder is 180prm, collect the extrudate for melt spinning, wherein the spinneret aperture is 0.3mm, and the nozzle draft ratio is 4.0, the obtained spun yarn is spread on the mesh curtain of the web forming machine, consolidated by a needle punching machine to obtain a rough geotextile, the tension is adjusted by a tension frame, and the raw geotextile enters a roll forming machine for edge trimming and roll forming to obtain a high temperature resistant geotextile. Figure 2 The scanning electron microscope image of the spinning obtained shows that the fibers present a continuous structure interpenetrating each other, with no obvious phase separation phenomenon and agglomeration of the inorganic filler.
[0104] Example 2
[0105] This embodiment provides a high temperature resistant geotextile and a preparation method thereof, wherein the high temperature resistant geotextile comprises the following components in parts by weight:
[0106]
[0107] The preparation method specifically comprises the following steps:
[0108] S1: Disperse polyetheretherketone in concentrated sulfuric acid to obtain a polyetheretherketone dispersion, wherein the mass ratio of polyetheretherketone to concentrated sulfuric acid is 1:15, stir, add p-phenylenediamine in a mass ratio of 4:100 to polyetheretherketone to obtain a pre-reaction solution, react at a constant temperature of 75°C for 4 hours to obtain a reaction solution A, pour it into deionized water and stir to obtain a pre-treated precipitate, wherein the volume ratio of reaction solution A to deionized water is 1:4, filter and wash until the pH of the supernatant is 7.2, and vacuum dry at 80°C for 10 h to obtain an amino polyether ether ketone intermediate; mixing the amino polyether ether ketone intermediate with maleic anhydride and dibenzoyl peroxide initiator to obtain a reaction solution B, wherein the mass ratio of the amino polyether ether ketone intermediate to maleic anhydride is 100:3.5, and the mass ratio of the amino polyether ether ketone intermediate to dibenzoyl peroxide initiator is 100:0.3, melting and reacting at 275° C. for 30 min under nitrogen protection at a flow rate of 100 mL / min, cooling and granulating to obtain a modified polyether ether ketone;
[0109] S2: polyethersulfone and N-methylpyrrolidone are mixed at a mass ratio of 1:12.5, 4-aminobenzoic acid is added to obtain a reaction solution C, wherein the mass ratio of polyethersulfone to 4-aminobenzoic acid is 100:4.5, and after stirring for reaction, the mixture is poured into deionized water, wherein the stirring temperature is 135°C and the time is 4 hours, and the pretreated polyethersulfone is obtained by filtration, and after washing, the mixture is vacuum dried at 70°C for 12 hours to obtain a carboxylated polyethersulfone intermediate; the carboxylated polyethersulfone intermediate is melt-mixed with glycidyl methacrylate under a nitrogen atmosphere, wherein the mass ratio of the carboxylated polyethersulfone intermediate to glycidyl methacrylate is 100:3.5, the melt-mixing temperature is 245°C, and the time is 15 minutes, and the modified polyethersulfone is obtained by cooling and granulation;
[0110] S3: Aluminum nitride and tetrahydrofuran are mixed in a mass ratio of 1:12, and dodecyl phosphate and triethylamine are added to obtain a reaction solution D, wherein the mass ratio of aluminum nitride to dodecyl phosphate is 100:3.5, and the mass ratio of aluminum nitride to triethylamine is 100:0.5. The mixture is stirred and reacted at 70°C for 5 hours, and a first modified aluminum nitride is obtained after centrifugal separation. The first modified aluminum nitride is dispersed in an acetonitrile solution of [BMIM]PF6 with a concentration of 2% to obtain a reaction solution E, wherein the mass ratio of the first modified aluminum nitride to is 100:2.3, and the mixture is subjected to an ultrasonic treatment at a power of 280 W for 1.5 hours, and then vacuum dried, wherein the vacuum drying temperature is 65°C and the time is 8 hours, to obtain a modified aluminum nitride;
[0111] S4: SiC powder is mixed with an ethanol / water mixed solution with a volume ratio of 8:2, wherein the mass ratio of SiC to the ethanol / water mixed solution is 1:15, polyvinyl pyrrolidone with a mass ratio of 1:100 to SiC is added to obtain a mixed solution, and after ultrasonic dispersion at a power of 380 W for 35 min, a mixed coupling agent is added to obtain a reaction solution F, wherein the mass ratio of KH550 to KH570 in the mixed coupling agent is 1:1, and the mass ratio of SiC to the mixed coupling agent is 100:3, and the reaction solution F is refluxed at 75° C. for 5 h, and centrifuged to obtain a first treated SiC, which is dispersed in a Tris buffer with a concentration of 0.05 M, wherein the solid-liquid mass ratio of the first treated SiC to the Tris buffer is 1:8, and dopamine hydrochloride is added, wherein the mass ratio of the first treated SiC to dopamine hydrochloride is 100:2.5, and the mixture is stirred at room temperature for 8 h, filtered, washed, and vacuum dried at 55° C. for 10 h to obtain modified SiC;
[0112] S5: Add modified polyetheretherketone, modified polyethersulfone and antioxidant 1076 into a high-speed stirrer for mixing, add modified silicon carbide and modified aluminum nitride to mix to obtain a mixture, add the mixture into a twin-screw extruder for extrusion, wherein the screw extrusion speed of the twin-screw extruder is 170prm, collect the extrudate for melt spinning, wherein the spinneret aperture is 0.2mm, and the nozzle draft ratio is 4.2, the obtained spun yarn is spread on the mesh curtain of the web forming machine, consolidated by a needle punching machine to obtain a rough geotextile, the tension is adjusted by a tension frame, and the raw geotextile enters a roll forming machine for edge trimming and roll forming to obtain a high temperature resistant geotextile.
[0113] Example 3
[0114] This embodiment provides a high temperature resistant geotextile and a preparation method thereof, wherein the high temperature resistant geotextile comprises the following components in parts by weight:
[0115]
[0116] The preparation method specifically comprises the following steps:
[0117] S1: Disperse polyetheretherketone in concentrated sulfuric acid to obtain a polyetheretherketone dispersion, wherein the mass ratio of polyetheretherketone to concentrated sulfuric acid is 1:20, stir, add p-phenylenediamine in a mass ratio of 3:100 to polyetheretherketone to obtain a pre-reaction solution, react at a constant temperature of 82°C for 6 hours to obtain a reaction solution A, pour it into deionized water and stir to obtain a pre-treated precipitate, wherein the volume ratio of reaction solution A to deionized water is 1:5, filter and wash until the pH of the supernatant is 6.5, and vacuum dry at 75°C for 11 h to obtain an amino polyether ether ketone intermediate; the amino polyether ether ketone intermediate is mixed with maleic anhydride and dibenzoyl peroxide initiator to obtain a reaction solution B, wherein the mass ratio of the amino polyether ether ketone intermediate to maleic anhydride is 100:2.5, and the mass ratio of the amino polyether ether ketone intermediate to dibenzoyl peroxide initiator is 100:0.7, and the reaction is carried out at 282° C. for 20 min under nitrogen protection at a flow rate of 150 mL / min, and the modified polyether ether ketone is obtained by cooling and granulation;
[0118] S2: polyethersulfone and N-methylpyrrolidone are mixed at a mass ratio of 1:14, 4-aminobenzoic acid is added to obtain a reaction solution C, wherein the mass ratio of polyethersulfone to 4-aminobenzoic acid is 100:4.2, and after stirring for reaction, the mixture is poured into deionized water, wherein the stirring temperature is 130°C and the time is 6 hours, and the pretreated polyethersulfone is obtained by filtration, and after washing, the mixture is vacuum dried at 68°C for 13.5 hours to obtain a carboxylated polyethersulfone intermediate; the carboxylated polyethersulfone intermediate is melt-mixed with glycidyl methacrylate under a nitrogen atmosphere, wherein the mass ratio of the carboxylated polyethersulfone intermediate to glycidyl methacrylate is 100:4, the melt-mixing temperature is 240°C, and the time is 17 minutes, and the modified polyethersulfone is obtained by cooling and granulation;
[0119] S3: Aluminum nitride and tetrahydrofuran are mixed in a mass ratio of 1:12, and dodecyl phosphate and triethylamine are added to obtain a reaction solution D, wherein the mass ratio of aluminum nitride to dodecyl phosphate is 100:4, and the mass ratio of aluminum nitride to triethylamine is 100:1.5, and the mixture is stirred and reacted at 65°C for 7 hours, and a first modified aluminum nitride is obtained after centrifugal separation, and the first modified aluminum nitride is dispersed in an acetonitrile solution of [BMIM]PF6 with a concentration of 1% to obtain a reaction solution E, wherein the mass ratio of the first modified aluminum nitride to is 100:2, and the mixture is ultrasonically treated at a power of 200 W for 1.8 hours, and then vacuum dried, wherein the vacuum drying temperature is 63°C and the time is 10 hours, to obtain a modified aluminum nitride;
[0120] S4: SiC powder was mixed with an ethanol / water mixed solution with a volume ratio of 9:1, wherein the mass ratio of SiC to the ethanol / water mixed solution was 1:10, polyvinyl pyrrolidone was added with a mass ratio of 1.8:100 to SiC to obtain a mixed solution, and after ultrasonic dispersion at a power of 300 W for 40 min, a mixed coupling agent was added to obtain a reaction solution F, wherein the mass ratio of KH550 to KH570 in the mixed coupling agent was 1.5:1, and the mass ratio of SiC to the mixed coupling agent was 1.5:1. The mass ratio is 100:2.8, reflux at 65°C for 7 hours, centrifuge to obtain the first treated silicon carbide, disperse it in a Tris buffer with a concentration of 0.09M, wherein the solid-liquid mass ratio of the first treated silicon carbide to the Tris buffer is 1:9, add dopamine hydrochloride, wherein the mass ratio of the first treated silicon carbide to dopamine hydrochloride is 100:1.5, stir at room temperature for 9.2 hours, filter, wash, and vacuum dry at 52°C for 12 hours to obtain modified silicon carbide;
[0121] S5: Add modified polyetheretherketone, modified polyethersulfone and antioxidant 1076 into a high-speed stirrer for mixing, add modified silicon carbide and modified aluminum nitride to mix to obtain a mixture, add the mixture into a twin-screw extruder for extrusion, wherein the screw extrusion speed of the twin-screw extruder is 180prm, 170prm, 150prm, 200prm, collect the extrudate for melt spinning, wherein the spinneret aperture is 0.3mm, 0.2mm, 0.4mm, 0.32mm, and the nozzle draft ratio is 4.0, 4.2, 3.8, 4.1, the obtained spun yarn is spread on the mesh curtain of the web forming machine, consolidated by a needle punching machine to obtain a rough geotextile, the tension is adjusted by a tension frame, and the raw geotextile enters a roll-forming machine for trimming and rolling to obtain a high temperature resistant geotextile.
[0122] Example 4
[0123] This embodiment provides a high temperature resistant geotextile and a preparation method thereof, wherein the high temperature resistant geotextile comprises the following components in parts by weight:
[0124]
[0125] The preparation method specifically comprises the following steps:
[0126] S1: Disperse polyetheretherketone in concentrated sulfuric acid to obtain a polyetheretherketone dispersion, wherein the mass ratio of polyetheretherketone to concentrated sulfuric acid is 1:19, stir, add p-phenylenediamine in a mass ratio of 3.5:100 to polyetheretherketone to obtain a pre-reaction solution, react at a constant temperature of 85°C for 5.4 hours to obtain a reaction solution A, pour it into deionized water and stir to obtain a pre-treated precipitate, wherein the volume ratio of reaction solution A to deionized water is 1:4.8, filter and wash until the pH of the supernatant is 7.5, and vacuum dry at 77°C 11.6h to obtain an amino polyether ether ketone intermediate; the amino polyether ether ketone intermediate is mixed with maleic anhydride and dibenzoyl peroxide initiator to obtain reaction solution B, wherein the mass ratio of the amino polyether ether ketone intermediate to maleic anhydride is 100:3.2, and the mass ratio of the amino polyether ether ketone intermediate to dibenzoyl peroxide initiator is 100:0.6, and the mixture is melt-reacted at 285°C for 28min under nitrogen protection at a flow rate of 140mL / min, and cooled and granulated to obtain modified polyether ether ketone;
[0127] S2: polyethersulfone and N-methylpyrrolidone are mixed at a mass ratio of 1:15, 4-aminobenzoic acid is added to obtain reaction solution C, wherein the mass ratio of polyethersulfone to 4-aminobenzoic acid is 100:3.5, and after stirring for reaction, the mixture is poured into deionized water, wherein the stirring temperature is 140°C and the time is 5.5 hours, and the pretreated polyethersulfone is obtained by filtration, and after washing, the mixture is vacuum dried at 60°C for 14 hours to obtain a carboxylated polyethersulfone intermediate; the carboxylated polyethersulfone intermediate is melt-mixed with glycidyl methacrylate under a nitrogen atmosphere, wherein the mass ratio of the carboxylated polyethersulfone intermediate to glycidyl methacrylate is 100:3, the melt-mixing temperature is 243°C, and the time is 16 minutes, and the modified polyethersulfone is obtained by cooling and granulation;
[0128] S3: Aluminum nitride and tetrahydrofuran are mixed in a mass ratio of 1:12, and dodecyl phosphate and triethylamine are added to obtain a reaction solution D, wherein the mass ratio of aluminum nitride to dodecyl phosphate is 100:3.8, and the mass ratio of aluminum nitride to triethylamine is 100:1.2. The mixture is stirred and reacted at 60°C for 6.2 hours, and a first modified aluminum nitride is obtained after centrifugal separation. The first modified aluminum nitride is dispersed in an acetonitrile solution of [BMIM]PF6 with a concentration of 1.7% to obtain a reaction solution E, wherein the mass ratio of the first modified aluminum nitride to is 100:2.7, and the reaction solution is subjected to ultrasonic treatment at a power of 300 W for 2 hours, and then vacuum dried, wherein the vacuum drying temperature is 55°C and the time is 9.4 hours, to obtain a modified aluminum nitride;
[0129] S4: SiC powder was mixed with ethanol / water mixed solutions with volume ratios of 7:3, 8:2, 9:1, and 8:2, wherein the mass ratio of SiC to the ethanol / water mixed solution was 1:14, polyvinyl pyrrolidone was added with a mass ratio of 2:100 to SiC to obtain a mixed solution, and after ultrasonic dispersion at a power of 400 W for 37 min, a mixed coupling agent was added to obtain a reaction solution F, wherein the mass ratio of KH550 to KH570 in the mixed coupling agent was 1.8:1, and the mass ratio of SiC to the mixed solution was 1:14. The mass ratio of the coupling agent is 100:2, and the first treated silicon carbide is obtained after reflux at 73°C for 6.4 hours and centrifugation, which is dispersed in a Tris buffer with a concentration of 0.1M, wherein the solid-liquid mass ratio of the first treated silicon carbide to the Tris buffer is 1:9.2, and dopamine hydrochloride is added, wherein the mass ratio of the first treated silicon carbide to dopamine hydrochloride is 100:2.2, and stirred at room temperature for 10 hours, filtered, washed, and vacuum dried at 45°C for 11.6 hours to obtain modified silicon carbide;
[0130] S5: Add modified polyetheretherketone, modified polyethersulfone and antioxidant 1010 into a high-speed stirrer for mixing, add modified silicon carbide and modified aluminum nitride to mix to obtain a mixture, add the mixture into a twin-screw extruder for extrusion, wherein the screw extrusion speed of the twin-screw extruder is 200prm, collect the extrudate for melt spinning, wherein the spinneret aperture is 0.32mm, and the nozzle draft ratio is 4.1, the obtained spun yarn is spread on the mesh curtain of the web forming machine, consolidated by a needle punching machine to obtain a rough geotextile, the tension is adjusted by a tension frame, and the raw geotextile enters a roll forming machine for trimming and rolling to obtain a high temperature resistant geotextile.
[0131] Comparative Example 1
[0132] This comparative example provides a high temperature resistant geotextile, which is different from Example 1 in that in step S1, the mass ratio of p-phenylenediamine to polyetheretherketone is adjusted to 7:100, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0133] Comparative Example 2
[0134] This comparative example provides a high temperature resistant geotextile, which is different from Example 1 in that in step S1, the mass ratio of p-phenylenediamine to polyetheretherketone is adjusted to 1:100, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0135] Comparative Example 3
[0136] This comparative example provides a high temperature resistant geotextile, which is different from Example 1 in that in step S2, the mass ratio of polyethersulfone to 4-aminobenzoic acid is adjusted to 100:9, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0137] Comparative Example 4
[0138] This comparative example provides a high temperature resistant geotextile, which is different from Example 1 in that in step S2, the mass ratio of polyethersulfone to 4-aminobenzoic acid is adjusted to 100:1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0139] Comparative Example 5
[0140] This comparative example provides a high temperature resistant geotextile, which is different from Example 1 in that in step S5, the mass portion of modified aluminum nitride is adjusted to 10 parts, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0141] Comparative Example 6
[0142] This comparative example provides a high temperature resistant geotextile, which is different from Example 1 in that in step S5, the mass portion of modified aluminum nitride is adjusted to 1 part, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0143] Comparative Example 7
[0144] This comparative example provides a high temperature resistant geotextile, which is different from Example 1 in that in step S5, the mass parts of modified silicon carbide are adjusted to 8 parts, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0145] Comparative Example 8
[0146] This comparative example provides a high temperature resistant geotextile, which is different from Example 1 in that in step S5, the mass portion of modified aluminum nitride is adjusted to 1 part, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0147] The performance test of the high temperature resistant geotextiles of the above-mentioned embodiments 1-4 and comparative examples 1-8 was carried out, and the specific process is as follows:
[0148] The tear strength of the test sample is tested according to GB / T 13763-2010;
[0149] According to GB / T 14800-2010, the CBR bursting strength of the test sample is tested;
[0150] The high temperature resistant geotextiles of the above-mentioned Examples 1-4 and Comparative Examples 1-8 were placed in an oven at 200° C. for 6 hours and then taken out to test their tear strength and CBR bursting strength.
[0151] The test results are shown in Table 1.
[0152] Table 1: Performance test results of high temperature resistant geotextiles of Examples 1-4 and Comparative Examples 1-8
[0153]
[0154] It can be seen from Table 1 that the high temperature resistant geotextiles prepared in Examples 1-4 provided by the present invention have good high temperature resistance and mechanical properties.
[0155] It can be obtained from the test results of Example 1 and Comparative Examples 1 and 2 that when the content of p-phenylenediamine is too high, excessive cross-linking leads to restricted segment movement, reduced processing performance, brittle fibers, and reduced mechanical properties of the resulting geotextile; when the content is too little, the degree of amination on the polyetheretherketone is low, the active sites are insufficient, and the subsequent maleic anhydride grafting rate is low, resulting in insufficient bonding with the filler, easy interface stratification, and reduced heat resistance.
[0156] From the test results of Example 1 and Comparative Examples 3 and 4, it can be obtained that when the addition amount of 4-aminobenzoic acid is too high, excessive substitution of sulfone groups leads to main chain breakage, and mechanical properties and thermal stability decrease; when the addition amount of 4-aminobenzoic acid is too low, the degree of carboxylation of polyethersulfone is insufficient, which is not conducive to the subsequent reaction with epoxy groups, resulting in a small number of polar groups, weak interfacial bonding with inorganic fillers, easy local deformation in high temperature environment, and reduced service life.
[0157] It can be seen from the test results of Example 1 and Comparative Examples 5-8 that adding appropriate amounts of modified aluminum nitride and modified silicon carbide can, when the addition amount of the two is too high, it is easy to disperse unevenly, causing agglomeration, forming stress concentration points, and also reducing the spinning performance, clogging the spinneret, and reducing the flexibility of the material; when the addition amount of the two is too low, the thermal conductivity and reinforcement effects of the material are not obvious, and the heat resistance is insufficient.
[0158] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a high temperature resistant geotextile, characterized in that: The preparation method comprises: S1: dispersing polyetheretherketone in concentrated sulfuric acid to obtain a polyetheretherketone dispersion, adding p-phenylenediamine after stirring to obtain a pre-reaction liquid, reacting at a constant temperature to obtain a reaction liquid A, pouring the reaction liquid A into deionized water and stirring to obtain a pre-treated precipitate, filtering, washing, and vacuum drying to obtain an amino polyetheretherketone intermediate; mixing the amino polyetheretherketone intermediate with maleic anhydride and dibenzoyl peroxide initiator to obtain a reaction liquid B, melting and reacting under nitrogen protection, cooling and granulating to obtain a modified polyetheretherketone; S2: Mixing polyethersulfone and N-methylpyrrolidone, adding 4-aminobenzoic acid to obtain reaction solution C, stirring the mixture to react, pouring the mixture into deionized water, filtering to obtain pretreated polyethersulfone, washing the mixture, and vacuum drying to obtain a carboxylated polyethersulfone intermediate; melt-mixing the carboxylated polyethersulfone intermediate with glycidyl methacrylate under a nitrogen atmosphere, cooling and granulating the mixture to obtain a modified polyethersulfone; S3: mixing aluminum nitride with tetrahydrofuran, adding dodecyl phosphate and triethylamine to obtain a reaction solution D, stirring the reaction, centrifuging to obtain a first modified aluminum nitride, dispersing the first modified aluminum nitride in an acetonitrile solution of [BMIM]PF6 to obtain a reaction solution E, ultrasonically treating the first modified aluminum nitride, and vacuum drying the first modified aluminum nitride. S4: mixing silicon carbide powder with an ethanol / water mixed solution, adding polyvinyl pyrrolidone to obtain a mixed solution, adding a mixed coupling agent after ultrasonic dispersion to obtain a reaction solution F, refluxing and centrifuging to obtain a first treated silicon carbide, dispersing it in a Tris buffer, adding dopamine hydrochloride, stirring at room temperature, filtering, washing, and vacuum drying to obtain a modified silicon carbide; S5: Add modified polyetheretherketone, modified polyethersulfone and antioxidant into a high-speed stirrer for mixing, add modified silicon carbide and modified aluminum nitride to mix to obtain a mixture, add the mixture into a twin-screw extruder for extrusion, collect the extrudate for melt spinning, lay the obtained spun yarn on the mesh curtain of a web forming machine, consolidate it through a needle punching machine to obtain a rough geotextile, adjust the tension through a tension frame, and enter a roll-forming machine for edge trimming and roll-forming to obtain a high temperature resistant geotextile.
2. The method for preparing a high temperature resistant geotextile according to claim 1, characterized in that: In S1: The mass ratio of the polyetheretherketone to concentrated sulfuric acid is 1:15-20; The mass ratio of p-phenylenediamine to polyetheretherketone is 3-4:100; The temperature of the pre-reaction liquid is 75-85°C; The pre-reaction solution is reacted at a constant temperature for 4-6 hours; The volume ratio of the reaction solution A to deionized water is 1:4-5; The pre-treated precipitate is washed until the pH of the supernatant is 6.5-7.5; The vacuum drying temperature is 70-80°C; The vacuum drying time is 10-12 hours.
3. The method for preparing a high temperature resistant geotextile according to claim 1, characterized in that: In S1: The mass ratio of the amino polyetheretherketone intermediate to maleic anhydride is 100:2.5-3.5; The mass ratio of the amino polyetheretherketone intermediate to the dibenzoyl peroxide initiator is 100:0.3-0.7; The temperature of the melting reaction of the reaction liquid B is 275-285°C; The melting reaction time of the reaction liquid B is 20-30min; The nitrogen flow rate is 100-150 mL / min.
4. The method for preparing a high temperature resistant geotextile according to claim 1, characterized in that: In S2: The mass ratio of polyethersulfone to N-methylpyrrolidone is 1:10-15; The mass ratio of the polyethersulfone to 4-aminobenzoic acid is 100:3.5-4.5; The stirring reaction temperature of the reaction solution C is 130-140°C; The stirring reaction time of the reaction solution C is 4-6h; The temperature of vacuum drying after washing the pretreated polyethersulfone is 60-70°C; The vacuum drying time after washing the pretreated polyethersulfone is 12-14 hours.
5. The method for preparing a high temperature resistant geotextile according to claim 1, characterized in that: In S2: The mass ratio of the carboxylated polyethersulfone intermediate to glycidyl methacrylate is 100:3-4; The temperature for melt mixing of the carboxylated polyethersulfone intermediate and glycidyl methacrylate is 235-245° C.; the time for melt mixing of the carboxylated polyethersulfone intermediate and glycidyl methacrylate is 15-20 minutes.
6. The method for preparing a high temperature resistant geotextile according to claim 1, characterized in that: In S3: The mass ratio of aluminum nitride to tetrahydrofuran is 1:10-15; The mass ratio of the aluminum nitride to the dodecyl phosphate is 100:3-4; The mass ratio of the aluminum nitride to triethylamine is 100:0.5-1.5; The stirring reaction temperature of the reaction solution D is 60-70°C; The stirring reaction time of the reaction solution D is 5-7h; The mass ratio of the first modified aluminum nitride to [BMIM]PF6 is 100:2-3; The concentration of the [BMIM]PF6 acetonitrile solution is 1-2%; The power of the ultrasonic treatment of the reaction solution E is 200-300W; The ultrasonic treatment time of the reaction solution E is 1-2h; The vacuum drying temperature is 55-65°C; The vacuum drying time is 8-10 hours.
7. The method for preparing a high temperature resistant geotextile according to claim 1, characterized in that: In S4: The volume ratio of ethanol to water in the ethanol / water mixed solution is 9:1-7:3; The mass ratio of the silicon carbide to the ethanol / water mixed solution is 1:10-15; The mass ratio of polyvinyl pyrrolidine to silicon carbide is 1-2:100; The ultrasonic power of the mixed solution is 300-400W; The ultrasonic time of the mixed solution is 30-40 min; The mass ratio of KH550 to KH570 in the mixed coupling agent is 1-2:1; The mass ratio of silicon carbide to mixed coupling agent is 100:2-3; The reflux temperature of the reaction solution F is 65-75°C; The reflux time of the reaction solution F is 5-7h.
8. The method for preparing a high temperature resistant geotextile according to claim 1, characterized in that: In S4: The concentration of the Tris buffer is 0.05-0.1M; The solid-liquid mass ratio of the first treated silicon carbide to the Tris buffer is 1:8-10; The mass ratio of the first treated silicon carbide to dopamine hydrochloride is 100:1.5-2.5; The stirring time at room temperature is 8-10h; The vacuum drying temperature is 45-55°C; The vacuum drying time is 10-12 hours.
9. The method for preparing a high temperature resistant geotextile according to claim 1, characterized in that: In S5: The antioxidant is antioxidant 1010 or antioxidant 1076; The screw extrusion speed is 150-200 rpm.
10. A high temperature resistant geotextile prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The high temperature resistant geotextile comprises the following components in parts by weight:
Citation Information
Patent Citations
Preparation method of sulfonated carbon nano tube grafted hydroxylated polyether-ether-ketone / polyether-ether-ketone composite material
CN105838086A
Aluminum nitride enhanced heatproof optical cable material and preparation method thereof
CN105936695A
Preparation method of high-strength anti-aging geotextile material
CN112575401A
CaCO3 grafted polyether sulfone modified epoxy resin composite material and preparation method thereof
CN114292564A
Method for improving interface performance of basalt fiber reinforced thermoplastic resin-based composite material
CN118461329A
Cited By
High-performance high-frequency flexible polyimide-based copper-clad plate and preparation method thereof
CN121157497A
High-performance high-frequency flexible polyimide-based copper-clad plate and preparation method thereof
CN121157497B